Utwór literacki jako dzieło sztuki (na podstawie wybranych dyskusji publicznych, odnotowanych w polskich czasopismach po 1989 roku) - Kuczera-Chachulska, Bernadetta (Colloquia Litteraria, 2011)
Literary work as a piece of art (based on selected public discussions as noted down in polish magazines after 1989) In the sketch the author raises the issue concerning the presence of a literary text in the contemporary social-media consciousness. At the outset the author draws two poles: the elite and egalitarian one, then, she passes to analysing public discourses which took place in the last century in cultural periodicals (“Znak”, “Tygodnik Powszechny”). One of the crucial conclusions of her observations is the judgement according to which a literary masterpiece has been in the last centuries as if less a piece of art and become more a place of exchanging a thought and social discourse.